GE_GERICHTE P/1286/2020 vom 10. Juli 2025 - GE Cour de justice (2025)
RECOURS JOINT;PRINCIPE DE L'ACCUSATION;ESCROQUERIE;TENTATIVE(DROIT PÉNAL);FAUX DANS LES CERTIFICATS | CP.251.ch1; CP.146; CP.22; CPP.401; CPP.9